Working at the crossroads: Statute Labour, Manliness, and the Electoral Franchise on Victorian Prince Edward Island - Grittner, Colin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
This essay considers how conceptions of manliness shaped the electoral franchise on Victorian Prince Edward Island. Soon after its institution of responsible government, Prince Edward Island shifted away from a property-based franchise to one grounded in the performance of statute labour. Instead of heralding the male property owner, this new law championed the man who used his labour to faithfully serve and improve his community. Because of limited land distribution, bourgeois ideals of manliness based upon property ownership fit the conditions of the colony poorly. A statute labour franchise better reflected the gender ideals upheld by the Island’s unpropertied majority. Like all gender ideals, these standards were not accepted across Prince Edward Island unopposed.